The effect of value innovation in the superior performance and sustainable growth of telecommunications sector : Mediation effect of customer satisfaction and loyalty - Hajar, Mohammed A.; Alkahtani, Ammar Ahmed; Daing Nasir, Ibrahim; Al-Sharafi, Mohammed A.; Alkawsi, Gamal; Noorminshah, A. Iahad; Mohd Ridzuan, Darun; Tiong, Sieh Kiong (MDPI, 2022)
The telecommunications industry has recognized innovation as the key to growth and survival. Globalization, liberalization, and privatization, the terms most commonly associated with this sector, have resulted in fierce competition, making it more difficult for telecommunications firms to increase their market share and, as a result, their customer base, sales volume, and, ultimately, profits. The new success strategy is differentiation through innovation, with the aim of breaking out of the competition and creating an uncontested market. This can be accomplished by providing high-value, innovative services that result in customer satisfaction and promote customer loyalty. The primary goal of this study was to create and validate a conceptual model of value innovation and its impact on firm performance and long-term growth by examining the mediation effect of customer satisfaction and loyalty. The empirical analysis results were based on 304 respondents who completed a paper-based survey provided to employees of Yemeni mobile service providers using a convenience non-probability sampling technique. SmartPLS 3 was used to test the hypothesized relationships using partial least squares structural equation modeling (PLS-PM). As a result, the findings empirically validated the theoretical research model, confirming the importance of the value innovation approach to achieving company performance and long-term growth by promoting customer satisfaction and loyalty. Finally, we have provided a discussion of the study’s theoretical contributions, managerial implications, and future research directions.